Bimbingan Individu Untuk Mengembangkan Penyesuaian Diri Istri Kepada Suami Tunanetra Non Bawaan di ITMI Kota Semarang - Nisa, Latifatun; Mintarsih, Widayat (Program Pascasarjana IAIN Langsa, 2024)
Negative stigma becomes problematic for wives who have husbands who are non-congenitally blind, thus affecting the developmental process of their adjustment. These obstacles cause a low sense of adjustment, less ready to accept the husband's condition, so it is necessary to provide individual guidance and motivation to them in an effort to improve their adjustment. This research aims to find out how individual guidance is implemented to increase the wife's adjustment to her non-congenital blind husband.The results of the research show that the stages of implementing individual guidance are, first, providing motivation to clients who are experiencing problems in life, creating inspiration for familiarity with clients. In the middle stage, the client has begun to know the solution to the problem, support from close friends and family. The final stage (follow-up) is carried out after the individual guidance activity is about to end, the supervisor carries out a follow-up plan and discusses success after carrying out individual guidance. The results of individual guidance achieved are: aspects of self-adjustment, firstly aspects of self-knowledge and self-insight, lack of awareness of interacting with disabilities to be able to interact with people with disabilities, lack of ability in having a relationship with husband to be able to accept and have a good relationship with husband, secondly aspects self-objectivity and self-acceptance, not being able to accept her husband's condition and not being able to be realistic in solving problems, becoming biased in accepting her husband's condition and thinking realistically in solving problems, the third aspect of self-development and self-control, lack of awareness of the importance of development in self-adjustment, becoming aware of the importance of adjustment yourself with your husband, always thinking about other people's negative views of the family, becoming not thinking about other people's negative views of the family, the four aspects of satisfaction, being less satisfied with their potential in improving their skills and understanding of their husband's needs, being able to increase their husband's potential skills and understanding.